Performance of the StaphGold ELISA test in determining subclinical Staphylococcus aureus infections in dairy cows using a Gaussian mixture model - Yang DA; Laven RA (John Wiley and Sons Ltd, 2022)
BACKGROUND: A novel ELISA test has been developed to detect antigen-specific IgG in early and late lactation cows in New Zealand. OBJECTIVES: This study was to evaluate the discriminatory ability of the ELISA based on the detection of S. aureus-specific IgG as a screening test. METHODS: The ELISA was used for the composite milk samples taken during routine herd testing in 2018-2019 milking season in New Zealand. In the absence of a gold standard test, the diagnostic specificity and sensitivity was estimated using a Gaussian mixture model. RESULTS: The ELISA test had a high accuracy (AUC = 0.98) to detect antigen-specific IgG in early and late lactation cows with high somatic cell count due to either subsequent to or contemporaneous with the S. aureus invasion. Using an S/P ratio = 0.3 as the cut-off value, the ELISA test has sensitivity of 0.9 and specificity of 0.95, while the sensitivity increased to 0.94 at a cost of a decreased specificity of 0.9 at a lower cut-off value 0.26. CONCLUSIONS: The integration of the ELISA test as a screening tool into specific control programs may be useful to reduce the spread of S. aureus infections, to aid with treatment decisions, and to establish a correct milking order.
Keywords: Staphylococcus aureus; dairy cattle; latent class analysis; receiver operating characteristic curve; serology; subclinical mastitis; unsupervised learning; Animals; Cattle; Cattle Diseases; Enzyme-Linked Immunosorbent Assay; Female; Immunoglobulin G; Mastitis, Bovine; Sensitivity and Specificity; Staphylococcal Infections; Staphylococcus aureus